No room at the morgue - Manchette, Jean-Patrick, 1942-1995 (New York review books classics, 2020)
"No Room at the Morgue came out after Jean-Patrick Manchette had transformed French crime fiction with such brilliantly plotted, politically charged, unrelentingly violent tales as Nada and The Mad and the Bad. Here, inspired by his love of Dashiell Hammett, Manchette introduces Eugene Tarpon, private eye, a sometime cop who has set up shop after being kicked off the force for accidentally killing a political demonstrator. Months have passed, and Tarpon desultorily tries to keep in shape while drinking all the time. No one has shown up at the door of his office in the midst of the market district of Les Halles. Then the bell rings and a beautiful woman bursts in, her hands dripping blood. It's Memphis Charles, her roommate's throat has been cut, and Memphis can't go to the police because they'll only suspect her. Can Tarpon help? Well, somehow he can't help trying. Soon bodies mount, and the craziness only grows"--